1998
DOI: 10.1111/j.2044-8333.1998.tb00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing resources and eyewitness suggestibility

Abstract: Purpose. Two experiments were conducted to test the hypothesis that encountering or retrieving suggested information under conditions of limited, rather than full, attentional resources is likely to increase false memory for suggested events. Methods. A typical eyewitness suggestibility paradigm was employed in which participants viewed a slide sequence depicting an office theft, answered misleading questions regarding the theft, and were later tested on their memory for the source of the suggested details. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 22 publications
4
46
0
Order By: Relevance
“…In list learning studies, information in the two sources (e.g., word lists 1 and 2) virtually never overlaps (for an exception, see Dodhia & Metcalfe, 1999), such that the two learning sources contain unique items (i.e., items studied in list 1 never appear in list 2 and vice versa, e.g., Bodner & Lindsay, 2003;Dobbins & McCarthy, 2008;Dodson, Holland, & Shimamura, 1998). However, in misinformation studies, items in the two sources almost always contain some degree of overlap, because the misinformation is presented in the context of the original event (Lane, Roussel, Villa, & Morita, 2007;Lindsay & Johnson, 1989;Zaragoza & Lane, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…In list learning studies, information in the two sources (e.g., word lists 1 and 2) virtually never overlaps (for an exception, see Dodhia & Metcalfe, 1999), such that the two learning sources contain unique items (i.e., items studied in list 1 never appear in list 2 and vice versa, e.g., Bodner & Lindsay, 2003;Dobbins & McCarthy, 2008;Dodson, Holland, & Shimamura, 1998). However, in misinformation studies, items in the two sources almost always contain some degree of overlap, because the misinformation is presented in the context of the original event (Lane, Roussel, Villa, & Morita, 2007;Lindsay & Johnson, 1989;Zaragoza & Lane, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…First, the effects of nonprobative photos tend to be more powerful for judgments about unfamiliar stimuli (Newman et al, 2012). Second, we wanted to make it difficult for people to encode the events well because the test phase happened soon after the study phase, and there is evidence that well-encoded experiences are less susceptible to the influence of nondiagnostic feelings than are poorly -encoded experiences (Monin, 2003;Zaragoza & Lane, 1998). The final set of animal names was a mix of mammals, reptiles, fish, and birds.…”
Section: Methodsmentioning
confidence: 99%
“…Later, Belli (1989) showed that McCloskey and Zaragoza's modified test was actually insensitive to memory impairment. In many ways, McCloskey and Zaragoza's most important contribution was to spark renewed interest in the area, the end result being that this new research advanced our knowledge of how postevent suggestions affect memory (Abeles & Morton, 1999;Belli, 1989;Frost, 2000;Lindsay, 1990;Loftus & Hoffman, 1989;Zaragoza & Lane, 1998;Zaragoza & McCloskey, 1989). What we discovered grew quickly, and by leaps and bounds.…”
Section: Final Commentsmentioning
confidence: 99%